Nomes relativos em Dzubukuá: análise diacrônica a partir dos termos de parentesco - Durazzo, Leandro Marques (2025)
This dissertation proposes a diachronic and historical-anthropological analysis of the contemporary reception of Dzubukuá, a language from the Karirí family, based on the reading of a colonial document, focusing on its internal linguistic structures, and emphasizing how they differ from Portuguese. The focus is directed towards discussing the difference between relative and absolute nouns in the language, using kinship terms as a case study. The methodology is based on comparing historical and contemporary sources to investigate possible diachronic non-indigenous influences on the autonomization of lexemes during scientific analyses of the language. Relationality and kinship in Karirí languages are discussed, exploring alienable possession and, from a linguistic and anthropological point of view, the impossibility of considering indigenous kinship terms as absolute nouns, in contrast to Portuguese. We substantiate the idea that indigenous kinship is, essentially, a system of relationships to, subsequently, deepen the analysis of relative and absolute nouns in Dzubukuá kinship, recovering considerations from pertinent literature on Karirí kinship. We argue that the absolutization of nouns in linguistic revitalization processes, without proper intercultural mediation, can obscure the indigenous linguistic and cultural logic as it is presented in the reference documents. In summary, we conclude that the diachronic and historical-anthropological analysis of kinship terms in Dzubukuá as documented by Bernardo de Nantes (1709) reveals a process of linguistic documentation influenced by Christian and colonial perspectives. For this reason, we advocate for the necessity of a linguistic-anthropological approach in indigenous language revitalization processes, which promotes critical awareness of the base materials and an intercultural reflection on didactic practices and corpus planning.